2003
DOI: 10.1073/pnas.2135255100
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of NF-κB-binding sites across human chromosome 22

Abstract: We have mapped the chromosomal binding site distribution of a transcription factor in human cells. The NF-B family of transcription factors plays an essential role in regulating the induction of genes involved in several physiological processes, including apoptosis, immunity, and inflammation. The binding sites of the NF-B family member p65 were determined by using chromatin immunoprecipitation and a genomic microarray of human chromosome 22 DNA. Sites of binding were observed along the entire chromosome in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
258
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(294 citation statements)
references
References 38 publications
29
258
0
7
Order By: Relevance
“…Most kB sites appear to be 10 bp in length with the consensus sequence 5 0 -GGGRN W YYCC-3 0 (where R denotes a purine base, N denotes any base, W denotes an adenine or thymine and Y denotes a pyrimidine base) (Sen and Baltimore, 1986;Chen and Ghosh, 1999). However, this degenerate kB DNA consensus sequence may still be more restrictive than what may be revealed by systematic in vitro (Linnell et al, 2004) and in vivo (Martone et al, 2003;Schreiber et al, 2006) studies. (However, in vivo studies do not distinguish between direct DNA-binding events and protein-protein interaction-mediated promoter association by NF-kB).…”
Section: Dna Target Sites Of Nf-kb Dimersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most kB sites appear to be 10 bp in length with the consensus sequence 5 0 -GGGRN W YYCC-3 0 (where R denotes a purine base, N denotes any base, W denotes an adenine or thymine and Y denotes a pyrimidine base) (Sen and Baltimore, 1986;Chen and Ghosh, 1999). However, this degenerate kB DNA consensus sequence may still be more restrictive than what may be revealed by systematic in vitro (Linnell et al, 2004) and in vivo (Martone et al, 2003;Schreiber et al, 2006) studies. (However, in vivo studies do not distinguish between direct DNA-binding events and protein-protein interaction-mediated promoter association by NF-kB).…”
Section: Dna Target Sites Of Nf-kb Dimersmentioning
confidence: 99%
“…Since then, high throughput technologies have revealed that the vast majority of the inflammatory gene expression program is NF-kBdependent (Hoffmann and Baltimore, 2006), and that DNA-bound NF-kB can be detected at many chromosomal locations (Martone et al, 2003;Schreiber et al, 2006). Given NF-kB's critical involvement in so many physiological responses, a major challenge of current research is to elucidate how NF-kB signaling in response to diverse stimuli can mediate distinct cellular responses in particular physiological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study, revealed that in dendritic cells TLR4 induced expression of inflammatory or T-cell stimulatory genes require distinct RelA or cRel subunits (Wang et al, 2007), suggesting that there is a regulatory code for canonical NF-κB dimers that remains to be elucidated. Given the abundance of NF-κB (more than 100,000 molecules per cell), it may not be surprising that genome-wide chromatin immunoprecipitation (ChIP) analysis revealed a large number of unexpected binding sites of unknown functional relevance (Martone et al, 2003;Schreiber et al, 2006). Therefore, such chromatin location studies must be coupled to functional analysis using genetic perturbations (knockouts and knock-in mutants) to elucidate the transcriptional regulatory code of NF-κB.…”
Section: Nf-κb Dependent Gene Expression During Immune Response Via Tmentioning
confidence: 99%
“…Several groups recently adapted this technology to identify transcription factor binding sites in human cells for selected regions of the human genome 3-5 . Two teams, one involving a collaboration between Affymetrix and Harvard 6 and the other at Yale 7,8 , have now extended this technology to map binding sites along entire human chromosomes.Martone et al 7 and Euskirchen et al 8 mapped the binding sites of NF-κB (p65) and CREB, respectively, along human chromosome 22, and Cawley et al 6 mapped the binding sites of Sp1, c-Myc and p53 on chromosomes 21 and 22. In each case, genomic tiling arrays were used.…”
mentioning
confidence: 99%
“…Several groups recently adapted this technology to identify transcription factor binding sites in human cells for selected regions of the human genome [3][4][5] . Two teams, one involving a collaboration between Affymetrix and Harvard 6 and the other at Yale 7,8 , have now extended this technology to map binding sites along entire human chromosomes.…”
mentioning
confidence: 99%